Iraq : First and Second Reviews of the Staff-Monitored Program and Request for a Three-year Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Iraq's First and Second Reviews of the Staff-Monitored Program (SMP) and Request for a Three-Year Stand-By Arrangement. The oil price decline has resulted in a massive reduction in Iraq's budget revenue, pushing the fiscal deficit to an unsustainable level. The authorities are responding to the crisis with a mix of necessary fiscal adjustment and financing, maintaining their commitment to the exchange rate peg. The authorities started an SMP in November 2015 to establish a track record of policy credibility and pave the way to a possible IMF financing arrangement. Their performance under the SMP has been broadly satisfactory.